Ответы и объяснения

2012-10-03T20:01:49+04:00

1) 7(2х+9)+3х=114

14х+63+3х=114

17х=114-63

17х=51

х=3

2) 3(4х+13)-25=74

12х+39=74+25

12х=99-39

12х=60

х=5

2012-10-03T20:02:50+04:00

7(2х+9)+3х=114                                               3(4х+13)-25=74

14х+63+3х=114                                                 12х+39-25=74

17х=114-63                                                       12х=74-39+25

17х=51                                                              12х=60

х=51:17                                                              х=60:12

х=3                                                                     х=5